Plane-by-Plane femtosecond laser inscription method for single-peak Bragg gratings in multimode CYTOP polymer optical fibre - Theodosiou, Antreas; Lacraz, Amédéé; Koutsides, Charalambos; Komodromos, Michael; Kalli, Kyriacos; Stassis, Andreas (My University, 2017)
We report on the development and characterization of single peak fiber Bragg gratings (FBGs) in polymer optical fiber (POF). We use a multimode gradient index cyclic transparent optical polymer (CYTOP) fiber, where the FBGs are inscribed with a femtosecond laser. We adapt the direct-write, plane-by-plane inscription method, where the beam is scanned transversely across the core, to create refractive index changes. In order to reduce the number of fiber modes coupling to the grating, we limit the FBG's spatial extent to the central part of the core, in the region where the gradient index profile peaks. In this way, we are able to excite the strongest lower order modes thereby generating single peak POF-FBG spectra. We support our experimental results with modeling using the bi-directional beam propagation method (Bi-BPM). Furthermore, a FBG array is used as a quasi-distributed sensor, recovering the vibration response of a freely suspended metal beam, using a 6-m sensing strand. The FBGs are multiplexed using a high-speed commercial wavelength demodulator, the output of which provides wavelength- and time-dependent displacement information. The results are compared directly with the performance of a silica-fiber-based FBG sensor array, and show a significant sensor sensitivity improvement for the polymer fiber to dynamic strain.
Keywords: Optical sensing and sensors; Polymer waveguides; Fiber optics sensors; Fibre Bragg gratings